Three key messages concerning the proposal for EU Soil Monitoring Law - Vainio, Eeva; Merilä, Päivi; Ilvesniemi, Hannu; Kekkonen, Hanna; Mäkipää, Raisa; Nieminen, Tiina M.; Pennanen, Taina; Tolvanen, Anne (Natural Resources Institute Finland (Luke), 2023)
Soil health is a prerequisite to food and water security, wood and fiber production, climate change mitigation and adaptation, and biodiversity. Thus, the sustainable use of soils is crucial for the maintenance of human wellbeing. The recently published proposal for EU Soil Monitoring Law supports the sustainable use of soils and facilitates effective measures to secure soil functions and ecosystem services. Still, there is a lot to do to combat the vicious cycle between deforestation, land degradation, biodiversity loss, decreased productivity, and climate change. Besides effective monitoring and relevant soil descriptors for soil health, new thinking and policy measures to support sustainable use of soils are needed.
Keywords: soil; sustainable use; land management